SELF-CARE AGENCY IMPROVES PERSONAL HYGIENE OF ELDERLY IN A NURSING HOME IN BINJAI [SELF-CARE AGENCY MENINGKATKAN PERSONAL HYGIENE PADA LANSIA DI PANTI WERDA BINJAI] - Lindawati Simorangkir; Endang Sinaga (Universitas Pelita Harapan, 2019)
The Self-Care Agency role is to increase knowledge with changing attitudes in driving the elderly to be more aware of the importance of personal hygiene in their daily lives. One attempt in the prevention of disease in the elderly is by doing personal hygiene so that the elderly can better feel comfort, safety and well-being. This study aimed to determine the effect of Self-Care Agency to the personal hygiene of the elderly in nursing home Binjai. The design study is Quasi-Experimental Design Time Series, with the approach of One Group Pre Post Test Design. Sampling was done by purposive sampling with a sample of 30 respondents. Research results pre intervention personal hygiene less category as much as 73%, and post intervention personal hygiene category of